Cybersecurity in Poland Legal Aspects. - Chałubińska-Jentkiewicz, Katarzyna; Radoniewicz, Filip; Zieliński, Tadeusz (Springer Nature, 2022)
This open access book explores the legal aspects of cybersecurity in Poland. The authors are not limited to the framework created by the NCSA (National Cybersecurity System Act - this act was the first attempt to create a legal regulation of cybersecurity and, in addition, has implemented the provisions of the NIS Directive) but may discuss a number of other issues. The book presents international and EU regulations in the field of cybersecurity and issues pertinent to combating cybercrime and cyberterrorism. Moreover, regulations concerning cybercrime in a few select European countries are presented in addition to the problem of collision of state actions in ensuring cybersecurity and human rights. The advantages of the book include a comprehensive and synthetic approach to the issues related to the cybersecurity system of the Republic of Poland, a research perspective that takes as the basic level of analysis issues related to the security of the state and citizens, and the analysis of additional issues related to cybersecurity, such as cybercrime, cyberterrorism, and the problem of collision between states ensuring security cybernetics and human rights. The book targets a wide range of readers, especially scientists and researchers, members of legislative bodies, practitioners (especially judges, prosecutors, lawyers, law enforcement officials), experts in the field of IT security, and officials of public authorities. Most authors are scholars and researchers at the War Studies University in Warsaw. Some of them work at the Academic Centre for Cybersecurity Policy - a thinktank created by the Ministry of National Defence of the Republic of Poland.
Keywords: Constitutional & administrative law.; Crime & criminology.; Criminal law & procedure.; Entertainment & media law.; Mass media.; Law.; Criminal law.; Administrative law.; Computer crimes.; Criminology.; Public safety.; Cybercrime; Cyberterrorism; NIS Directive; Open access; Operational reconnaissance; Right to privacy